Resilience of logistic service providers facing a port strike: a case study - Brum, Luís Teotónio van Zeller Pamplona do Canto (2014)
The purpose of this thesis is to study the impact of a port strike on companies that perform as logistic service providers in a supply chain (SC), here denominated 3PL (third-party logistic providers). These companies are highly dependent on ports to perform their activity, since they provide international services. Consequently, a disruption in a port can seriously impair their business. A stevedores’ strike is one of the possible disruptions that can affect ports. This study aims to analyze the negative effects caused by this disruption, and what strategies 3PLs may implement in order to keep their performance levels stable and have a quick recovery time. Within this objective, the first step will be to establish a theoretical context about the maritime port’s sector and 3PLs in a SC context, to then expand the concept of a resilient SC, and finally to develop a theoretical framework in order to better contextualize the case study. Subsequently, the impact of a port strike will be quantified by using a case study comprising three companies, covering the areas of land and sea distribution and port operations. Information from primary sources was assembled in two phases: first via e-mail and, in a second phase, through a personal interview. The information from secondary sources was obtained through television news, internet and conferences, enabling its cross-analysis. Finally, by analyzing the collected data, it will be possible to draw conclusions about the measures carried out by each company to minimize the negative effects of the strike, thus contributing to a more resilient SC. As a conclusion, a stevedores’ strike will create a snow-ball of negative effects in the SC, degrading all relevant KPIs (key performance indicators) of the 3PLs under study. No mitigation and contingency strategies available proved really effective to reduce the negative effects of a port strike disruption.